2018
DOI: 10.1186/s12939-018-0902-1
|View full text |Cite
|
Sign up to set email alerts
|

“I feel more comfortable speaking to a male”: Aboriginal and Torres Strait Islander men’s discourse on utilizing primary health care services

Abstract: BackgroundAboriginal and Torres Strait Islander men have the highest morbidity and mortality rates, and lowest rates of health service utilization in Australia. There is a current perception that Aboriginal and Torres Strait Islander men are disinterested in their health. This study aimed to identify the perceived motivators, barriers and enablers of Aboriginal and Torres Strait Islander men’s utilization of primary health care services, explore their experiences and obtain suggestions from them as to how serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
113
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(118 citation statements)
references
References 16 publications
1
113
0
4
Order By: Relevance
“…The available data detailing Aboriginal and Torres Strait Islander health service use is patchy 17,18 ; however, most indicates that Aboriginal and Torres Strait Islander men use PHCSs at lower rates than their female counterparts, especially for preventative healthcare. Many authors suggest Aboriginal and Torres Strait Islander men tend to delay care, often presenting at a time of advanced or serious illness 1,10,11,19 . Yet, access and utilisation are a function of multiple, complex and interacting factors that enable (or inhibit) Aboriginal and Torres Strait Islander men from accessing and using available care.…”
Section: Health Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…The available data detailing Aboriginal and Torres Strait Islander health service use is patchy 17,18 ; however, most indicates that Aboriginal and Torres Strait Islander men use PHCSs at lower rates than their female counterparts, especially for preventative healthcare. Many authors suggest Aboriginal and Torres Strait Islander men tend to delay care, often presenting at a time of advanced or serious illness 1,10,11,19 . Yet, access and utilisation are a function of multiple, complex and interacting factors that enable (or inhibit) Aboriginal and Torres Strait Islander men from accessing and using available care.…”
Section: Health Seekingmentioning
confidence: 99%
“…Currently, Aboriginal and Torres Strait Islander men are viewed as being disinterested in their health, thus, the blame is being placed on the individuals themselves for their under‐utilisation of PHCSs. In contrast to this misconception, studies have found that Aboriginal and Torres Strait Islander men are interested in their health but many face significant barriers that hinder access 1–7 . In response, Aboriginal and Torres Strait Islander men have identified strategies for PHCSs to reduce barriers and increase their use, which fundamentally includes working with local men to develop innovative strategies 1,5‐7 …”
mentioning
confidence: 99%
“…This may be reflected in primary health care service reports, records and Medicare claims, but it cannot be further from the truth. Instead, Aboriginal and Torres Strait Islander men are interested in their health and want to engage with primary health care services, and herein lies the challenge . Health services must be willing to ask the Aboriginal and Torres Strait Islander men of their community how they want to utilise the service and how it, in turn, can better accommodate and respond to their hopes, wants and needs.…”
mentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander men need to and want to define their own future, which is critical to turning this situation around . A recent qualitative study presented the perspectives of Aboriginal and Torres Strait Islander men on their motives, barriers and enablers regarding their utilisation of primary health care services . Addressing some of the barriers identified would be a good starting point.…”
mentioning
confidence: 99%
See 1 more Smart Citation